Integration of islamic values and educational psychology in bullying prevention in islamic boarding schools: A literature study on the role of teachers as moral guides - Oktoberi, Rezki; Musfiroh, Siti; Syandra, Syifa Hanifah; Amiruddin, Amiruddin; Amalia, Tin (ARKA INSTITUTE, 2025)
The prevalence of bullying among students poses a particular challenge for educators in Islamic boarding schools in preventing bullying through educational strategies based on Islamic values with an educational psychology approach. This study aims to analyze the integration of Islamic values and educational psychology principles in efforts to prevent bullying in Islamic boarding schools. Through a literature review of 12 recent national and international studies, it was found that effective bullying prevention efforts require a comprehensive approach, not only oriented towards discipline, but also towards character building and the emotional health of students. Islamic values such as tauhid, akhlak, and ihsan serve as moral and spiritual foundations, while educational psychology theories—including emotion regulation, social learning, and moral development—provide a practical framework for understanding and guiding students’ behavior. The results of the study show that teachers in Islamic boarding schools have a strategic role as holistic murabbi who serve as spiritual role models, emotional counselors, and social facilitators. Recommended strategies include enriching the character curriculum based on empathy and conflict resolution, implementing a whole-school and whole-boarding approach, and training teachers in Islamic value-based psychopedagogical interventions. This integrative model is believed to be capable of forming a supportive and empathetic pesantren culture, while reducing the risk of bullying behavior among santri.